Bioconversion of Banana, Mustard Greens, and Chicken Meat Waste Using Black Soldier Fly Larvae - Agus Kurniawan Putra; Nurqomaria Nurqomaria; Nur Santy Asminaya; Serlin Serlin; Puspita Puspita (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Waste is leftover material from daily human activities that is no longer used and natural processes in solid form. Like other cities in Indonesia, the volume of waste in Kendari City has increased along with the increase in population. The largest contributors to waste in the city of Kendari come from household waste (80.96%) and market waste (9.33%). This research aims to determine the conversion power of waste through the use of BSF as a natural, environmentally friendly waste-converting agent. The method used in this research is a preexperimental method using BSF larvae to reduce mustard greens, bananas, and chicken meat waste. The research showed that the growth rate of BSF larvae on mustard greens media stopped on day 15 because some of the larvae had become pupae, whereas on chicken meat waste, it stopped on day 12, and on banana waste, it stopped on day 27. The average growth rate of BSF larvae The highest was found in mustard green waste media (0.11 grams/head), followed by banana waste (0.08 gr/head) and chicken meat waste media (0.03 gr/head). The highest average percentage of substrate consumption was banana waste (23.37%), followed by mustard green waste (22.1%) and chicken meat waste (15.33%). The highest average Waste Reduction Index percentage was found in banana market waste (7.79%), followed by mustard greens waste (7.37%) and chicken meat waste (5.11%). This research indicates that BSF larvae are suitable as a bioconversion agent for mustard greens, bananas, and chicken meat waste.